Biogas production from ensiled meadow grass; effect of mechanical pretreatments and rapid determination of substrate biodegradability via physicochemical methods. (April 2015) - Tsapekos, P.; Kougias, P.G.; Angelidaki, I.
Highlights: Methane production from untreated and pretreated ensiled meadow grass was examined. Mechanical pretreatments improved the ensiled meadow grass biodegradability. The most efficient pretreatment method enhanced the methane yield by 25%. EC, SCOD and EH have been tested for rapid determination of the methane production. Among the three methods, EC showed the best calibration statistics. Abstract: As the biogas sector is rapidly expanding, there is an increasing need in finding new alternative feedstock to biogas plants. Meadow grass can be a suitable co-substrate and if ensiled it can be supplied to biogas plants continuously throughout the year. Nevertheless, this substrate is quite recalcitrant and therefore efficient pretreatment is needed to permit easy access of microbes to the degradable components. In this study, different mechanical pretreatment methods were applied on ensiled meadow grass to investigate their effect on biomass biodegradability. All the tested pretreatments increased the methane productivity and the increase ranged from 8% to 25%. The best mechanical pretreatment was the usage of two coarse mesh grating plates. Additionally, simple analytical methods were conducted to investigate the possibility of rapidly determining the methane yield of meadow grass. Among the methods, electrical conductivity test showed the most promising calibration statistics ( R 2 = 0.68).